DEVELOPING COURSES IN THE BEHAVIOURAL AND SOCIAL SCIENCES FOR MEDICAL STUDENTS: NEW PROSPECTS FOR AN OLD PROBLEM - Peter J.Blizard, Peter J.Blizard (Universitas Gadjah Mada, 1976)
This paper described methods which can be used to construct